Thermal deformations and brightness temperature of the ice cover of freshwater bodies - S. V. Tsyrenzhapov; A. A. Gurulev (Лëд и снег)
The paper presents results of experimental studies of the deformation of a freshwater ice cover. The works were carried out on the Lake Arakhley located in the Trans-Baikal Region, where winters are characterized by small amount of snow and sharp daily changes in the air temperature reaching 25 °C. As a result of this, the temperature gradient of the surface layer of the ice cover exceeds 1 °C/cm. This causes formation of the dry cracks in the upper layers of the cover. The authors measured daily variations in the temperature of the ice cover at various depths by its thickness. Results of the experiment made possible to propose the explanation for the formation of dry cracks and the depth of them, which reaches 20 cm in the Trans-Baikal Region. According to studies using a differential strain gauge, it was found that the upper layer of the ice cover is in a stressed state due to changes in its temperature. This is evident from the fact that when the temperature of the upper layer of ice changes, the distance between the reference points slightly changes too. When the air temperature approaches the temperature of the «ice–water» phase transition, the ice cover is unloaded. We assume that the dry cracks can also be formed when the stress state of ice is released at even lower temperatures. Interest in these structural changes had been arisen in connection with possible variations in the electromagnetic properties of the ice cover, which can be detected by non-contact radio wave measurements. These variations result from the presence of a quasiliquid layer on the surfaces of dry cracks (together with hoar-frost and snow in them), which can exist down to a temperature of −90 °C. Its presence increases the complex relative permittivity of a medium consisting of a solid (ice) and a liquid phase (water film). Calculations of the radiometric temperature within the centimeter range in a flat-layer non-isothermal medium have shown that the presence of dry cracks in the ice cover increases radio temperature up to 5 K on both, vertical and horizontal polarizations. This value is recorded during radiometric measurements, and this factor should be taken into account during the remote sensing of freshwater ice covers.